ANALISIS FUNDAMENTAL PADA HARGA SAHAM GOCAP YANG TERDAFTAR DI BURSA EFEK INDONESIA - Alya Ummus Syuhada; Muji Gunarto (JURNAL ILMIAH EDUNOMIKA, 2024)
The purpose of this study is to test hypotheses and produce empirical evidence regarding the effect of Net Profit Margin (NPM), Return On Assets (ROA), Return On Equity (ROE), Return On Investment (ROI), Earning Per Share (EPS), Price Earning Ratio (PER) and Price to Book Value (PBV) to Gocap's share price. This study uses secondary data accessed through www.idx.co.id And application Data Share Indonesia with see report finance annual period 2022. Population Study This as much 866 Company in Exchange Effect Indonesia. Taking sample done use technique purposive sampling with total sampleas much 67 sample. Engineering Method Analysis data Which used is quantitative And partial Least Square (PLS) with program SmartPLS version 4.0. The results of this study are expected to increase the researcher's understanding of the basics that form the basis for making investment decisions for an investor in the capital market and are expected to be a reference for other parties interested in conducting similar research in the future.